Efisiensi Makan Spodoptera exigua (Lepidoptera: Noctuidae) pada Bawang Daun, Sawi Hijau dan Seledri di Laboratorium - Hariani, Nova; Ahmad, Intan; Rahayu, Resti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
The aim of this research is to gain further understanding of how particular insect species respons to different host plants. This research isconsidered as preliminary research in integrated pest management for Spodoptera exigua. We report herein the consumption and utilizationof green onion (Allium fistulosum), caisin (Brassica rapa subsp. Parachinensis) and celery (Apium graveolens) by Spodoptera exigua. Theevaluation of indices of food consumption, growth and food utilization showed that caisin (Brassica rapa subsp. Parachinensis) was the bestfood for the last instar larvae of S. exigua as compared with celery or green onion. Growth rates and efficiency of conversion of ingestedfood to biomass (ECI) were significantly higher for larvae fed caisin (11.93%) than for those given green onion (8.06%) or celery (7.74%)Although the protein content of caisin (2.23%) was a bit lower than that of green onion (2.45%) but higher than celery (1.28%), we suspectthat the larvae performed best in caisin due to good balance between protein and carbohydrate as well as water content in caisin as comparedwith other host plants.